Fabrication of Cu2O Nanostructured Thin Film by Anodizing - Voon, Chun Hong; Lim, Bee Ying; Gopinath, Subash Chandra Bose; Al-Douri, Yarub; Foo, Kai Long; Md Arshad, Mohd Khairuddin; Ten, Seng Teik; Ruslinda, A. Rahim; Hashim, Uda; Tony, Voo Chung Sung (De Gruyter Open, 2018)
Cuprous oxide, a narrow bandgap p-type semiconductor, has been known as a potential material for applications in supercapacitors, hydrogen production, sensors, and energy conversion due to its properties such as non-toxicity, easy availability, cost effectiveness, high absorption coefficient in the visible region and large minority carriers diffusion length. In this study, Cu2O nanostructured thin film was fabricated by anodizing of Cu plates in ethylene glycol containing 0.15 M KOH, 0.1 M NH4F and 3 wt.% deionized water. The effects of anodizing voltage and temperature of electrolyte were investigated and reported. It was found that nanoporous Cu2O thin film was formed when anodizing voltages of 50 V and 70 V were used while a dense Cu2O thin film was formed due to the aggregation of smaller nanoparticles when 30 V anodizing voltage was used. Nanoplatelets thin film was formed when the temperature of electrolyte was reduced to 15 °C and 5 °C. X-ray diffraction confirmed the presence of Cu2O phase in thin film formed during anodizing of Cu plates, regardless of the anodizing voltage and temperature of electrolyte. Photoluminescence spectroscopy showed the presence of Cu2O peak at 630 nm corresponding to band gap of 1.97 eV. A mechanism of the formation of Cu2O thin film was proposed. This study reported the ease of tailoring Cu2O nanostructures of different morphologies using anodizing that may help widen the applications of this material.